2019
DOI: 10.2147/cmar.s228887
|View full text |Cite
|
Sign up to set email alerts
|

<p>T-Regulatory Cells In Tumor Progression And Therapy</p>

Abstract: Regulatory T cells (Tregs) are important members of the immune system regulating the host responses to infection and neoplasms. Tregs prevent autoimmune disorders by protecting the host-cells from an immune response, related to the peripheral tolerance. However, tumor cells use Tregs as a shield to protect themselves against anti-tumor immune response. Thus, Tregs are a hurdle in achieving the complete potential of anti-cancer therapies including immunotherapy. This has prompted the development of novel adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 175 publications
(187 reference statements)
1
51
0
1
Order By: Relevance
“…However, the abscopal effect is rarely observed in treatment of cancers by RT alone, both in preclinical models and in clinical practice. Recently, Honjo et al and Allison et al discovered PD-1 and CTLA-4 antibodies, respectively, which have revolutionized treatments for patients with multiple metastases in various types of cancers, providing a durable long-term response [ 11 , 12 , 13 , 14 , 15 , 16 ]. However, the response is observed for only up to 30% of patients [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the abscopal effect is rarely observed in treatment of cancers by RT alone, both in preclinical models and in clinical practice. Recently, Honjo et al and Allison et al discovered PD-1 and CTLA-4 antibodies, respectively, which have revolutionized treatments for patients with multiple metastases in various types of cancers, providing a durable long-term response [ 11 , 12 , 13 , 14 , 15 , 16 ]. However, the response is observed for only up to 30% of patients [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Honjo et al and Allison et al discovered PD-1 and CTLA-4 antibodies, respectively, which have revolutionized treatments for patients with multiple metastases in various types of cancers, providing a durable long-term response [ 11 , 12 , 13 , 14 , 15 , 16 ]. However, the response is observed for only up to 30% of patients [ 11 , 12 , 13 , 14 , 15 , 16 ]. Together with the radiation-induced abscopal effect, combined therapy with immune checkpoint blockade has been found to be an effective strategy for some cancers [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], although the optimal combination strategy, especially in the context of radiation delivery (e.g., sequence, total dose, and fractionation) remains unclear for some types of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…An exception is represented by tumors in which there is a strong inflammatory component, where the presence of the Tregs is beneficial (62). They are considered for inhibition through different strategies (60,62) (Table I). B lymphocytes.…”
Section: Cd4 + T Lymphocytes They Are In Different States Of Polarizmentioning
confidence: 99%
“…PD-L1 and CTLA-4 function in peripheral tolerance by activating regulatory T-cells and inhibiting the effector T-cells [ 194 , 195 ]. In mice models, anti-CD134 and anti-CD25 monoclonal antibodies successfully reduced the number of regulatory T-cells within the peripheral lymphoid tissue and caused the regression of tumors [ 196 , 197 ]. Moreover, a complete response was only found in the combination of anti-CD25 and anti-PD-1 [ 196 ].…”
Section: Mechanisms Of Resistance To Immunotherapy and Ways To Ovementioning
confidence: 99%
“…On the other hand, the combination of anti-PD-1 with anti-CD134 had a negative effect on the immune system and reduced survival in mouse models [ 198 ]. Studies conducted in rodents showed that targeting folate receptor 4 with monoclonal antibodies led to T reg depletion [ 197 ].…”
Section: Mechanisms Of Resistance To Immunotherapy and Ways To Ovementioning
confidence: 99%